High-strength spring steel with excellent delayed fracture resistance and heat treatment process thereof

By using specific chemical composition ratios and heat treatment processes in spring steel, the composite structure is formed, and the problem of delayed fracture caused by hydrogen is solved, which significantly improves the strength and delayed fracture resistance of the steel, ensuring the safety of long-term service.

CN119685715AActive Publication Date: 2025-03-25NANJING IRON & STEEL CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411630971.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-25
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

Existing spring steels are prone to hydrogen-induced delayed fracture problems during the high-strength process, which is difficult to ensure the safety of long-term service.

Method used

Specific chemical composition ratios and heat treatment processes are adopted, including quenching heat treatment, first rapid tempering treatment and second tempering treatment, to form a composite structure to improve the resistance to delayed fracture.

Benefits of technology

The tensile strength, yield strength and delayed fracture resistance of spring steel are significantly improved, ensuring the safety and durability of steel under long-term stress.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses high-strength spring steel with excellent delayed fracture resistance and a heat treatment process of the high-strength spring steel, and relates to the technical field of steel production. 1.60% to 2.20% of Si; 0.80% to 1.30% of Mn; 0.80% to 1.30% of Cr; 0.10% to 0.20% of W; 0.15% to 0.30% of V; 0.015% to 0.035% of Nb; p: less than or equal to 0.012%; s: less than or equal to 0.010%; o < = 0.0015%; n is less than or equal to 0.0060%; h < = 0.00012; and the balance of iron and inevitable impurities. Compared with comparison steel, the mechanical property and the delayed fracture resistance of the spring steel are remarkably improved under the same treatment process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of steel production, and in particular to a high-strength spring steel with excellent delayed fracture resistance and a heat treatment process thereof. Background Art

[0002] Springs are important safety bearing components. With the rapid development of industries such as automobiles, railways, and engineering machinery, in order to reduce weight and save energy, higher and higher requirements are placed on the strength level of spring steel. However, the improvement of the strength level of steel often brings more prominent hydrogen-induced delayed fracture problems, which has become a major obstacle to further strengthening high-strength steel. The delayed fracture phenomenon is a kind of environmental embrittlement caused by the long-term interaction of material-environment (hydrogen)-stress, and is a form of hydrogen-induced material deterioration (hydrogen damage or hydrogen embrittlement). Even in a static state without running, springs used in automobiles, railway trains, etc. need to withstand the long-term effect of their own body weight load, and spring steel is mostly quenched + medium-temperature tempering to obtain medium-temperature tempered martensite structure, so it has a higher risk of delayed fracture. Even if the spring adopts protective treatment such as surface coating, it is inevitably damaged by factors such as flying stones, bumps and reciprocating deformation during long-term service. Hydrogen generated by corrosion at the damaged part still has a greater risk of inducing delayed fracture. Therefore, in recent years, delayed fracture resistance design has received more and more attention in the research and development of spring steel.

[0003] The invention patent with application number 202010147746.0, "An ultra-high strength spring steel with excellent resistance to hydrogen-induced delayed fracture and its production method", mainly controls Al / N ≥ 3.5 to obtain fine austenite grains (≤ 10 μm) and cementite size (≤ 25 μm), so as to obtain excellent delayed fracture resistance and fatigue life. Although the refinement of grain size and cementite can increase the density of hydrogen traps, both grain boundaries and cementite are reversible hydrogen traps. Under long-term stress, the adsorbed hydrogen can still diffuse and enrich to the stress concentration site, making it difficult to ensure the safety of long-term service.

[0004] The invention patent with application number 202311430070.6, "A high-strength spring steel with hydrogen embrittlement resistance and delayed fracture performance, and its heat treatment method and production method", proposes the use of isothermal partitioning + medium-temperature tempering heat treatment process to obtain a dual-phase structure of martensite + carbide-free bainite + residual austenite. However, the more residual austenite in this structure often transforms into martensite under long-term stress, which not only seriously affects the elastic reduction performance of the spring steel and causes the spring height to decrease, affecting safe service, but also the newly transformed martensite has a high carbon content and is not tempered, so it is very brittle and still has a great risk of delayed fracture.

[0005] The invention patent "A hydrogen embrittlement-resistant high-strength spring steel and its heat treatment method" with application number 202210549788.6 proposes to add higher contents of Ni (2.8~3.5 wt.%), Cu (1.3~2.0 wt.%) and Al (0.9~1.30 wt.%), and control Ni / Cu≤3, Al / Cu≤1, so as to maintain fine NiAl and Cu precipitation phases with a coherent relationship with the matrix during the tempering process. However, the addition of a higher content of Cu in the steel can easily cause copper brittle cracking, and the high Al content can also easily form a large number of coarse Al oxide inclusions (because they precipitate during the steel smelting and solidification process), which seriously deteriorates the fatigue properties of the spring steel. In addition, the high content of precious elements such as Ni and Mo affects the economy of the steel and is not suitable for mass production applications. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the disadvantages of the prior art and provide a high-strength spring steel with excellent delayed fracture resistance and a heat treatment process thereof.

[0007] In order to solve the above technical problems, the technical solution of the present invention is as follows: A high-strength spring steel with excellent delayed fracture resistance, the chemical composition and mass percentage of which are as follows: C: 0.50%~0.60%; Si: 1.60%~2.20%; Mn: 0.80%~1.30%; Cr: 0.80%~1.30%; W: 0.10%~0.20%; V: 0.15%~0.30%; Nb: 0.015%~0.035%; P: ≤0.012%; S: ≤0.010%; O≤0.0015%; N≤0.0060%; H≤0.00012; the rest are iron and unavoidable impurities.

[0008] As a preferred embodiment of the high-strength spring steel with excellent delayed fracture resistance according to the present invention, the mass percentages of V, Nb, W and N satisfy the relationship: 0.25≤0.80V(%)+[Nb(%)-6.64N(%)]+W≤0.40.

[0009] The present invention also provides a heat treatment process for high-strength spring steel with excellent delayed fracture resistance, which sequentially comprises: quenching heat treatment, first tempering heat treatment and second tempering heat treatment; Wherein, the heating temperature of the quenching heat treatment is 900±30°C, and the holding time is 30±10 min.

[0010] As a preferred solution of the heat treatment process of the high-strength spring steel with excellent delayed fracture resistance of the present invention, the cooling method of the quenching heat treatment is oil cooling or water cooling.

[0011] As a preferred solution of the heat treatment process of the high-strength spring steel with excellent delayed fracture resistance according to the present invention, the first tempering heat treatment comprises: Heat to 580±20 ℃ at a heating rate of 50±10 ℃ / s, keep warm for 20±5 s and then cool with water.

[0012] As a preferred solution of the heat treatment process of the high-strength spring steel with excellent delayed fracture resistance of the present invention, the tempering temperature of the second tempering heat treatment is 350±20°C, and the holding time is 90-120 min.

[0013] As a preferred solution of the heat treatment process of the high-strength spring steel with excellent delayed fracture resistance of the present invention, the cooling method of the second tempering heat treatment is air cooling or water cooling.

[0014] The beneficial effects of the present invention are: The spring steel produced by the present invention is forged into a diameter F After controlled cooling, the 16 mm bar can obtain mechanical properties such as tensile strength ≥2050 MPa, yield strength ≥1800 MPa, elongation after fracture ≥10%, cross-sectional shrinkage ≥45%, and room temperature impact energy (KV2) ≥17 J, showing good strength, plasticity and toughness combination; delayed fracture resistance (characterized by tensile strength after saturated hydrogen charging) ≥1250 MPa, which is more than 30% higher than the conventional spring steel 60Si2CrV. The spring steel of the present invention has significantly improved mechanical properties and delayed fracture resistance compared with the comparative steel under the same processing technology. DETAILED DESCRIPTION

[0015] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific implementation methods.

[0016] The present application provides a high-strength spring steel with excellent delayed fracture resistance, whose chemical composition and mass percentage are as follows: C: 0.50%~0.60%; Si: 1.60%~2.20%; Mn: 0.80%~1.30%; Cr: 0.80%~1.30%; W: 0.10%~0.20%; V: 0.15%~0.30%; Nb: 0.015%~0.035%; P: ≤0.012%; S: ≤0.010%; O≤0.0015%; N≤0.0060%; H≤0.00012; the rest are iron and unavoidable impurities.

[0017] The mass percentages of V, Nb, W, and N elements in the composition of the above-mentioned high-strength spring steel satisfy the relationship: 0.25≤0.80V(%)+[Nb(%)-6.64N(%)]+W≤0.40; wherein V(%), Nb(%), W(%), and N(%) represent the mass percentages of V, Nb, W, and N, respectively.

[0018] The above spring steel is smelted in an electric arc furnace or converter + refining outside the furnace, cast into ingots or continuous casting into billets, and then forged or rolled into rods and wires, and rolled into diameters. F For 15 mm steel bars, after heat treatment, the tensile strength of the material shall be ≥2050 MPa, the yield strength shall be ≥1800 MPa, the elongation after fracture shall be ≥10%, the cross-sectional shrinkage shall be ≥45%, the room temperature V-type impact energy shall be ≥17 J, and the delayed fracture resistance shall be more than 30% higher than that of existing spring steels.

[0019] The role and proportion of each element in this application are as follows: C: C is necessary for spring steel to obtain high strength, hardness and elasticity. In order to obtain the required high strength level after quenching and tempering, the C content must be above 0.50%. However, too high a C content is not good for plasticity and toughness, increases decarburization sensitivity, and deteriorates the fatigue performance and processing performance of steel. Therefore, the C content should be controlled at 0.50-0.60%.

[0020] Si: Si has a strong solid solution strengthening effect, and also significantly improves the elasticity reduction resistance of spring steel by refining carbides. However, too high Si content will reduce plastic toughness, promote decarburization and graphitization tendency of steel during rolling and heat treatment, make smelting difficult and easy to form inclusions, and deteriorate the fatigue resistance of steel. Considering that strong carbide forming elements V and Nb can alleviate the above-mentioned adverse effects of Si, the Si content is controlled to 1.60-2.20%.

[0021] Mn: Mn can improve the hardenability of steel, and has a significant solid solution strengthening effect when dissolved in ferrite. It is also an effective element for deoxidation and desulfurization. When the content is less than 0.80%, it is difficult to play the above role. However, when quenched steel is tempered, Mn and P have a strong tendency to co-segregate at the grain boundaries, which deteriorates the toughness and delayed fracture resistance of the steel. Therefore, the Mn content is controlled below 1.30%.

[0022] Cr: Cr can significantly improve the hardenability and tempering resistance of steel; at the same time, Cr can also reduce the activity of C, reduce the surface decarburization of steel during heating, rolling and heat treatment, and inhibit the graphitization tendency of high Si steel, which is useful for obtaining high fatigue resistance. However, too high a content will deteriorate the elasticity and toughness of steel, so the Cr content is controlled to 0.80-1.30%.

[0023] W: W element can improve the hardenability of steel, reduce temper brittleness, and improve the elasticity reduction resistance of steel; W, V, C, and N can form (W, V) (C, N) nano-carbides together and can serve as effective hydrogen traps to improve delayed fracture resistance. However, excessive W affects the economic efficiency of steel, so the preferred W content range is 0.10-0.20%.

[0024] V: V is a strong carbide-forming element. The fine dispersed carbides formed by combining with C can not only prevent the grain growth during heating, play a role in fine grain strengthening, thereby improving the strength, toughness and fatigue performance of steel at the same time, but also act as an effective hydrogen trap to inhibit the diffusion and enrichment of hydrogen to stress concentration areas. When the V content is lower than 0.15%, the above effect is not obvious; when the V content is higher than 0.30%, the above effect is saturated and the cost of steel is increased. Therefore, the V content is controlled to be 0.15-0.30%.

[0025] Nb: Nb has a strong bonding force with C and N. The Nb (C, N) formed has a very effective grain refinement effect, which not only improves the strength and toughness of steel, but also is a very effective hydrogen trap to improve the delayed fracture resistance of steel. However, the strengthening effect of excessive Nb is no longer obvious, and it increases the crack sensitivity of steel, so it is controlled at 0.015~0.035%.

[0026] P: P can form micro segregation when the molten steel solidifies, and then segregate at the grain boundaries when heated to the austenitizing temperature, which significantly increases the brittleness of the steel, so the P content is controlled below 0.012%.

[0027] S: An inevitable impurity in steel. The formation of MnS inclusions and segregation at grain boundaries will deteriorate the toughness and fatigue resistance of the steel, so its content is controlled below 0.010%.

[0028] O: O forms various oxide inclusions in steel, which deteriorates the mechanical properties of steel, especially toughness and fatigue resistance. Therefore, measures must be taken to reduce its content as much as possible in metallurgical production. Considering economic efficiency, its content is controlled below 0.0015%.

[0029] N: N mainly forms Nb and V carbonitride M(C,N) with Nb and V in steel, which refines grains and improves delayed fracture resistance. Too high N content will significantly reduce the cold working performance of steel, so its content is controlled below 0.0060%.

[0030] H: If H is too high in steel, it will not only cause internal defects in the ingot, but also seriously deteriorate the delayed fracture resistance of the steel. Therefore, it is controlled below 0.00012%.

[0031] In addition, in order to ensure good ductility and delayed fracture resistance while obtaining ultra-high strength, V+Nb+W composite alloying is used. On the one hand, a higher austenitizing temperature can be used to dissolve most of the V carbonitride V(C, N), so that it can be re-precipitated as nano-scale M(C, N) during the subsequent high-temperature tempering process to play the role of precipitation strengthening and effective hydrogen trap; on the other hand, there is a proper amount of undissolved Nb(C, N) to inhibit grain growth during austenitizing heating to obtain a fine martensite structure; secondly, adding a proper amount of W element accelerates the precipitation of M(C, N). Therefore, its content must also meet the parameters i Relationship: 0.25≤0.80V(%)+[Nb(%)-6.64N(%)]+W≤0.40, θ=0.80V(%)+[Nb(%)-6.64N(%)]+W. When the θ value is less than 0.25, even though the contents of the individual V and Nb elements may be within the above most suitable range, good toughness and delayed fracture resistance cannot be obtained; when the θ value is greater than 0.40, the effect is saturated and the cost of steel is increased.

[0032] In order to obtain excellent elasticity and elastic resistance, spring steel is usually tempered at medium temperature after quenching to obtain medium temperature tempered martensite (also known as tempered troostite). However, V (C, N) is difficult to disperse and precipitate in large quantities during the medium temperature tempering process, that is, the traditional spring steel heat treatment process is difficult to exert the precipitation strengthening and effective hydrogen trap effect of V element carbonitride. In this regard, the present application also provides a heat treatment method for ultra-high strength spring steel with excellent delayed fracture resistance, the heat treatment method comprising the following steps: 1) Quenching heat treatment to obtain uniform quenched martensite structure and dissolve most of V (C, N) into the matrix structure, wherein the quenching austenitization heating temperature is 900 ± 30 °C, the holding time is 30 ± 10 min, and the cooling method is oil cooling or water cooling; 2) The first rapid induction tempering heat treatment is performed to obtain more nano-scale V(C, N) precipitation phases, wherein the steel is heated to 580±20°C at a heating rate of 50±10°C / s, kept at this temperature for 20±5 s, and then water-cooled; 3) The second tempering heat treatment is to obtain the medium-temperature tempered martensite (tempered troostite) structure, where the tempering temperature is 350 ± 20 °C, the holding time is 90-120 min, and the cooling method is air cooling or water cooling. Considering the high temperature of the first rapid tempering treatment, the temperature of the second conventional tempering treatment is lowered to obtain the required strength level.

[0033] In specific production applications, the ultra-high strength steel of the present invention can be smelted in an electric arc furnace or a converter + refining outside the furnace, cast into ingots or continuously cast into billets, and then forged or rolled into rods, wires and other products. In the technical solution of this application: (1) Microalloying elements V+Nb are added to the steel to ensure that as many nano-scale M(C, N) precipitation phases as possible are obtained as effective hydrogen traps in advance of obtaining a fine grain size, and also have the effect of precipitation strengthening; (2) Two tempering treatments are used, that is, the first rapid high-temperature tempering treatment obtains the nano-scale M(C, N) precipitation phase, and the second tempering treatment temperature is lower than the conventional tempering temperature to precipitate a large number of fine ε-carbides and obtain a good precipitation strengthening effect, so as to ensure that the ultra-high strength is obtained while still having good plasticity and toughness.

[0034] The following is further described by means of specific examples.

[0035] Sample preparation: According to the chemical composition range designed by the present invention, 3 furnaces of the present steel and 3 furnaces of comparative steel were smelted in a vacuum induction furnace, of which 1 furnace was the commonly used 60Si2CrV spring steel, and its specific chemical composition is shown in Table 1, of which furnaces No. 1# to No. 3 were the present steel, and furnaces No. 4# to No. 6 were comparative steels, of which No. 6 was the commonly used 60Si2CrV spring steel. The steel ingots were forged into a diameter of F 15mm rods are slowly cooled after forging. Processed into standard room temperature tensile specimens required for the experiment according to national standards (gauge section diameter d 0=5mm, length l 0=5 d 0), Charpy V-type impact specimen (10 mm × 10 mm × 55 mm). Heat treatment was performed according to the heat treatment process shown in Table 1. The delayed fracture resistance of the steel was evaluated according to GB / T39039-2020 "Evaluation method for hydrogen-induced delayed fracture of high-strength steel". In the specific production process, the corresponding steel can be obtained by using the corresponding preparation process.

[0036]

[0037] Table 1 Performance Testing: The samples were subjected to tensile and impact tests at room temperature and the results are listed in Table 2.

[0038]

[0039] Table 2 It can be seen from Table 2 that the steel of the present invention is forged into a diameter FAfter controlled cooling, the 16 mm bar can obtain mechanical properties such as tensile strength ≥2050 MPa, yield strength ≥1800 MPa, elongation after fracture ≥10%, cross-sectional shrinkage ≥45%, and room temperature impact energy (KV2) ≥17 J, showing good strength, plasticity and toughness combination; delayed fracture resistance (characterized by tensile strength after saturated hydrogen charging) ≥1250 MPa, which is more than 30% higher than the conventional spring steel 60Si2CrV. The mechanical properties and delayed fracture resistance of the steel of the present invention are significantly improved compared with the comparative steel under the same processing technology.

[0040] In addition to the above embodiments, the present invention may also have other implementation modes; any technical solutions formed by equivalent replacement or equivalent transformation shall fall within the protection scope required by the present invention.

Claims

1. A high-strength spring steel having excellent delayed fracture resistance, characterized in that: Its chemical composition and mass percentage are as follows: C: 0.50%~0.60%; Si: 1.60%~2.20%; Mn: 0.80%~1.30%; Cr: 0.80%~1.30%; W: 0.10%~0.20%; V: 0.15%~0.30%; Nb: 0.015%~0.035%; P: ≤0.012%; S: ≤0.010%; O ≤0.0015%; N ≤0.0060%; H ≤0.00012; the rest are iron and unavoidable impurities.

2. The high-strength spring steel having excellent delayed fracture resistance according to claim 1, characterized in that: In the high-strength spring steel with excellent delayed fracture resistance, the mass percentages of V, Nb, W and N satisfy the relationship: 0.25≤0.80V(%)+[Nb(%)-6.64N(%)]+W≤0.

40.

3. A heat treatment process for the high-strength spring steel with excellent delayed fracture resistance according to claim 1, characterized in that: Including in order: Quenching heat treatment, first tempering heat treatment and second tempering heat treatment; Wherein, the heating temperature of the quenching heat treatment is 900±30°C, and the holding time is 30±10 min.

4. The heat treatment process of high-strength spring steel with excellent delayed fracture resistance according to claim 3, characterized in that: The cooling method of the quenching heat treatment is oil cooling or water cooling.

5. The heat treatment process of high-strength spring steel with excellent delayed fracture resistance according to claim 3, characterized in that: The first tempering heat treatment comprises: Heat to 580±20 ℃ at a heating rate of 50±10 ℃ / s, keep warm for 20±5 s and then cool with water.

6. The heat treatment process of high-strength spring steel with excellent delayed fracture resistance according to claim 3, characterized in that: The tempering temperature of the second tempering heat treatment is 350±20°C, and the holding time is 90-120 min.

7. The heat treatment process of high-strength spring steel with excellent delayed fracture resistance according to claim 3, characterized in that: The cooling method of the second tempering heat treatment is air cooling or water cooling.

Citation Information

Patent Citations

  • Ultrahigh-strength spring steel with excellent hydrogen-induced delayed fracture resistance and production method thereof

    CN111321346A

  • Hydrogen embrittlement-resistant high-strength spring steel and heat treatment method thereof

    CN114908302A

  • High-strength corrosion-resistant spring steel and manufacturing method thereof

    CN105886930A

  • Method for manufacturing steel for high-strength hollow spring

    CN107148483A

  • Heat-resistant spring steel with tensile strength larger than 2100 MPa and production method thereof

    CN111748739A